2020
DOI: 10.1017/s0016756820000199
|View full text |Cite
|
Sign up to set email alerts
|

The Tumblagooda Sandstone revisited: exceptionally abundant trace fossils and geological outcrop provide a window onto Palaeozoic littoral habitats before invertebrate terrestrialization

Abstract: The establishment of permanent animal communities on land was a defining event in the history of evolution, and one for which the ichnofauna and facies of the Tumblagooda Sandstone of Western Australia have been considered an archetypal case study. However, terrestrialization can only be understood from the rock record with conclusive sedimentological evidence for non-marine deposition, and original fieldwork on the formation shows that a marine influence was pervasive throughout all trace fossil-bearing strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…The palaeogeographic and tectonic context of the Mereenie Sandstone thus favour that it was deposited some distance from any marine influence, with a high perched water table due to local groundwater flow, which rose further as the basin centre continued to subside (Shaw et al, 1991). In light of this assessment, the ichnofauna of the succession may have global significance in comparison with known Silurian-Devonian continental ichnofaunas from settings that retained some marine connectivity (Draganits et al, 2001;Krapovickas et al, 2016;Shillito & Davies, 2020).…”
Section: Regional Sedimentary Contextmentioning
confidence: 93%
See 2 more Smart Citations
“…The palaeogeographic and tectonic context of the Mereenie Sandstone thus favour that it was deposited some distance from any marine influence, with a high perched water table due to local groundwater flow, which rose further as the basin centre continued to subside (Shaw et al, 1991). In light of this assessment, the ichnofauna of the succession may have global significance in comparison with known Silurian-Devonian continental ichnofaunas from settings that retained some marine connectivity (Draganits et al, 2001;Krapovickas et al, 2016;Shillito & Davies, 2020).…”
Section: Regional Sedimentary Contextmentioning
confidence: 93%
“…Palaeomagnetic studies have suggested that it was most likely deposited between the early Silurian and the Early Devonian (with the caveat that signals may have been overprinted) (Li et al, 1991). Gouramanis and McLoughlin (2016) favoured a late Silurian to Early Devonian age for the unit, based on comparison with other trace fossil-bearing strata across Australia: although ichnostratigraphic age estimates must be treated with caution (Egenhoff et al, 2007;Buatois & Mángano, 2011;Davies et al, 2011;Mángano et al, 2012), especially as the units with which it was compared (Tumblagooda Sandstone, Major Mitchell Sandstone, Mount Daubeny Formation, Ravendale Formation) are themselves not directly dated (Cayley & Taylor, 1997;Neef & Bottrill, 2001;Neef, 2004;McNamara, 2014;Shillito & Davies, 2020).…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Facies 8 bedding planes, which archive intricately preserved sedimentary surface textures that formed at the time of deposition, can be defined as ''true substrates'' (Davies and Shillito 2018). Recent work attests that the preservation of such high-resolution original morphology requires no unusual circumstances, with the occasional preservation of true substrates an inevitability of the interplay between the ordinariness, sedimentary stasis, and spatial variation that sculpt the siliciclastic record (e.g., Miall 2015;Tipper 2015;Davies et al 2017Davies et al , 2019Shillito and Davies 2020). Notions that delicate sedimentary surface textures (e.g., adhesion marks, ripple marks) require the aid of microbial cohesion of sediment for preservation (in the Rawnsley Quartzite and elsewhere) (e.g., Gehling 2000;Seilacher 2008;Sarkar et al 2011;Sappenfield et al 2017;Bradley et al 2018;MacNaughton et al 2019) are unnecessary.…”
Section: Facies 7: Multidirected Trough-and Planar-stratified Sandstonementioning
confidence: 99%
“…to be an environmental stress that resulted in low diversity or diminutive ichnofaunas in late Paleozoic strata (Buatois et al, 2006;Jackson et al, 2016). However, the Matjiesgoedkloof ichnofauna differs from expectations as it is similar to non-glacial shallow marine strata elsewhere in the Table Mountain Group (Rust, 1967;Braddy and Almond, 1999), and some of its most prominent ichnotaxa are archetypal constituents of other lower Paleozoic Gondwanan sandy littoral environments in non-glacial settings (e.g., Heimdallia and Diplichnites : Shillito and Davies, 2020). The similarities between the glacial Matjiesgoedkloof ichnofauna and its nonglacial contemporaries resembles trends observed in modern settings, where comparable ichnofauna occur in both arctic and temperate littoral settings and it is position on the high-low tidewater transect that chiefly controls specific ichnoassemblages (Aitken et al, 1988).…”
Section: Salinity Dilution Of Marine Waters Through Glacial Melting H...mentioning
confidence: 99%